ADVANCEMENTS IN MICRONEEDLE TECHNOLOGY: COMPREHENSIVE INSIGHTS INTO VERSATILE DRUG DELIVERY MECHANISMS - SEKAR, LOKESWAR; SEENIVASAN, RAAGUL; REDDY, M. VIVEK; VARMA, K. DILEEP; AHMED, SYED SUHAIB; PACHIYAPPAN, JEY KUMAR; GANESH, GNK (International Journal of Applied Pharmaceutics, 2024)
Microneedle-based transdermal medication administration is a revolutionary drug delivery technique that has advantages over parenteral and oral drug delivery systems. They are convenient, painless, safe, and effective. Due to the skin’s stratum corneum layer, the majority of drugs only have a limited impact, which constitutes a thickness of about 10 to 15 µm and acts as a barrier for molecules to reach the site of action, allowing just a few molecules to pass through. To overcome this, many researchers have concentrated on using microneedles to bypass the stratum corneum barrier. The main goal of microneedles is to get the drug into the epidermis without disrupting nerve endings. Micron-sized channels created by the skin layer being broken by microneedles transport the medication directly to the epidermis or higher dermis, avoiding the barrier layer and into the systemic circulation. As a result, the microneedle can improve transdermal drug delivery. Microneedles are fabricated in different forms, such as “Solid Microneedles,” “Coated Microneedles,” “Dissolving or Biodegradable Microneedles,” “Hollow Microneedles” and Hydrogel-forming Microneedles, through the use of components including polymers, polysaccharides, silicon, and metals. Micromolding, laser cutting, dip coating, 3D printing and its techniques are just a few of the processes used to make microneedles. Recently, microneedles have become popular for delivering drugs, genes, proteins, RNA and vaccines, demonstrating significant therapeutic effects. A variety of nano-carriers, along with different delivery methods, assist in emphasizing the use of microneedles in the meantime.